Ograniczenia w przeprowadzaniu licytacji nieruchomości wynikające z art. 952(1) Kodeksu postępowania cywilnego - Marszelewska, Dominika (Kortowski Przegląd Prawniczy, 2022)
COVID-19 pandemic caused number of adjustments in Polish law, including the scope of enforcement law regulation. The Polish law provides many ways for creditors to seek redress. One of the ways and at the same time the most complicated and complex is the enforcement from real estate owned by the debtor. Current situation however, indicates that the need to protect the debtor in relation to meeting his or her basic life needs is not insignificant. This paper attempts to discuss the addition of Article 952(1) to the Code of Civil Procedure. The presented restrictions under the indicated provision relate to special rules for conducting auctions of real estate used to satisfy the debtor's housing needs. As it turns out, this provision causes numerous interpretation problems in the practice of enforcement authorities.